Segmentation of tuberculosis bacilli in Ziehl-Neelsen tissue slide images using Hibrid Multilayered Perceptron network - M. K., Osman; Mohd Yusoff, Mashor, Prof. Madya Dr.; Jaafar, H. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/